Dialeteísmo versus abordagem epistêmica: o caso do paradoxo do mentiroso - RODRIGUES, Jéssica Gonçalves (2025)
In classical logic, a contradiction is always false. However, although in classical logic contradictions result in falsehoods, they emerge in a variety of scenarios, from medical and scientific disputes to mathematical contexts. In order to deal with these contradictory situations without making the system trivial (i.e. without accepting that everything is true), formal paraconsistent systems have been developed. A system is considered paraconsistent when it violates the law of explosion, which states that from any contradiction any sentence can be inferred. The emergence of these systems was crucial for the the advent of different interpretations of contradiction, such as Graham Priest’s dialectical approach by Graham Priest (2006a; 2006b). This view supports the existence of contradictions especially evidenced by paradoxes such as the Liar paradox. Paradoxes, such as the Liar, can be seen as arguments made up of apparently true premises, which follow apparently valid steps and arrive at an apparently unacceptable conclusion (a contradiction). In the dialectical view, a paradox is taken as a valid argument and therefore we must accept that its conclusion (a contradiction) is true. These are contradictions whose status is disputable. Unlike this kind of contradiction, there are those that are not true and that occur in different contexts, such as some geometric contradictions, which are based on misleading figures. These, in turn, are contradictions whose status is not disputable, because they are easy to solve. Alternatively to dialetheism, there are approaches that reject the idea of true contradictions, offering alternative interpretations. In this context, we will explore the epistemic view of Carnielli and Rodrigues (2019a; 2020), who consider contradictions as epistemically conflicting, but not conclusive. Thus, in this view, true contradictions are intolerable. With this in mind, the aim of this dissertation is to examine how the aforementioned approaches address contradictions, such as in the case of the Liar Paradox, evaluating their limitations and the extent to which they can be considered rivals.